Health insurance transitions and use of fringe banks: Evidence from the Affordable Care Act. (21st April 2020) - Fitzpatrick, Anne; Fitzpatrick, Katie
Abstract: The Affordable Care Act (ACA) increased health insurance enrollment, potentially improving financial security. We test whether this insurance increase relates to changes in use of "fringe banks" (e.g., payday lenders, check cashers, and pawn shops). Using the panel structure of the Current Population Survey (CPS), we link 5 years of a Federal Deposit Insurance Corporation (FDIC)‐sponsored supplement to March CPS data. We find declines in fringe bank use, specifically fringe credit (e.g., pawn loans), associated with new insurance coverage with larger declines for households affected by the ACA's Medicaid expansion. These results suggest that health insurance reduces reliance on these controversial financial products.